2021
DOI: 10.1155/2021/6690523
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Modifications of Neuronal Plasticity

Abstract: Nucleosomes composed of histone octamer and DNA are the basic structural unit in the eukaryote chromosome. Under the stimulation of various factors, histones will undergo posttranslational modifications such as methylation, phosphorylation, acetylation, and ubiquitination, which change the three-dimensional structure of chromosomes and affect gene expression. Therefore, the combination of different states of histone modifications modulates gene expression is called histone code. The formation of learning and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…In addition to histone acetylation, changes in histone methylation marks were reported in the brain of aged mice, including decreased methylation in H3K27me3, H3R2me2, H3K79me3, and H4K20me2 (Gong et al, 2015). These findings support that both types of histone marks are deeply involved in brain aging and age-related cognitive functions (Geng et al, 2021). It should be emphasized that two recent separate studies demonstrated that downregulation of H3K9me3 and transcriptional de-repression of LINE1 are important features of brain aging in mice and monkeys (Zhang et al, 2021e;Zhang et al, 2022e).…”
Section: Molecular Changessupporting
confidence: 54%
“…In addition to histone acetylation, changes in histone methylation marks were reported in the brain of aged mice, including decreased methylation in H3K27me3, H3R2me2, H3K79me3, and H4K20me2 (Gong et al, 2015). These findings support that both types of histone marks are deeply involved in brain aging and age-related cognitive functions (Geng et al, 2021). It should be emphasized that two recent separate studies demonstrated that downregulation of H3K9me3 and transcriptional de-repression of LINE1 are important features of brain aging in mice and monkeys (Zhang et al, 2021e;Zhang et al, 2022e).…”
Section: Molecular Changessupporting
confidence: 54%
“…Many studies have linked histone modifications such as methylation, phosphorylation and acetylation, in promoting modifications to neurogenesis, neuronal plasticity and behavioural adaptation in response to the environmental stimuli and developmental signals (reviewed in Ref. 70). For instance, H3K4 methylation is required for the increased transcriptional activity of neurogenesis-related genes, while H3K27 and H3K36 methylation affects the pluripotency of neural progenitor cells and dictates their neural lineage specification and differentiation 70–72.…”
Section: Histones In Brain Developmentmentioning
confidence: 99%
“…70). For instance, H3K4 methylation is required for the increased transcriptional activity of neurogenesis-related genes, while H3K27 and H3K36 methylation affects the pluripotency of neural progenitor cells and dictates their neural lineage specification and differentiation 70–72. Crosstalk between histone acetylation and deacetylation also influences glial cell fate 73.…”
Section: Histones In Brain Developmentmentioning
confidence: 99%
“…In addition, many amino acid residues in histones can be methylated, and different types of methylation, such as monomethylation (me 1), dimethylation (me 2) and trimethylation (me 3), show a variety of valence states. Changes in histone methylation patterns may promote or inhibit gene expression ( Geng et al, 2021 ). Different histone modification types also influence each other to jointly regulate the expression of specific genes.…”
Section: Mechanisms Of Epigenetic Regulationmentioning
confidence: 99%